2015
DOI: 10.1007/s10433-015-0348-x
|View full text |Cite
|
Sign up to set email alerts
|

Social engagement across the retirement transition among “young-old” adults in the French GAZEL cohort

Abstract: The objective of this study was to test predictors of change in social engagement across the retirement transition in a cohort of 10,692 French utility workers retiring between 1992 and 2004, aged 51-65 in 2004. Three measures of social engagement (organizational activity participation, number of close family members, and number of close friends) were collected in 1991 and 2004; 1991 scores were subtracted from 2004 scores to determine change. We used ordered logistic regression to model predictors of change. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
3
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(38 citation statements)
references
References 33 publications
2
30
3
3
Order By: Relevance
“…The proportion of elderly women and men differed among countries, influencing their representation in the samples of the studies. While studies on aging generally involve more women than men, the present review identified a number of studies with a higher proportion of men than women 9,16,21,26 . In addition, some studies investigated only women or only men 19,[28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The proportion of elderly women and men differed among countries, influencing their representation in the samples of the studies. While studies on aging generally involve more women than men, the present review identified a number of studies with a higher proportion of men than women 9,16,21,26 . In addition, some studies investigated only women or only men 19,[28][29][30][31][32] .…”
Section: Discussionmentioning
confidence: 99%
“…Less frequent was the observation that levels of social engagement remain stable throughout life, including in old age 18,20,21,24,37 . The results of these studies point to the existence of continuity in relation to the social behaviors that are constructed and nourished throughout life and therefore influence outcomes in old age.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nos primeiros anos após aposentar-se é provável que ocorra uma ampliação das relações sociais em função do maior tempo livre para realizar atividades com outras pessoas (Sabbath, Lubben, Goldberg, Zins, & Berkman, 2015). Entretanto, há evidências de que esse movimento não permanece acontecendo no transcorrer dos anos, em virtude do encolhimento no tamanho das redes gerado a partir das limitações físicas que podem emergir com a idade (Cornwell, Laumann, & Schumm, 2008;Marcum, 2013).…”
Section: Dinâmica De Funcionamento Das Redes Sociais No Processo De Aunclassified